Underfill material, semiconductor package, and method for manufacturing semiconductor package
The underfill material, comprising epoxy resin, aromatic amine hardener, inorganic filler, and specific triazine ring-containing compounds, addresses the challenges of pot life stability and high-temperature adhesion to copper, providing enhanced reliability for semiconductor packages.
Patent Information
- Application Number
- JP2021572717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-23
- Filing Date
- 2021-01-18
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-01-18
AI Technical Summary
Existing underfill materials for semiconductor packages face challenges with pot life stability and high-temperature adhesion to copper, particularly when using compounds with excellent copper adhesion, which can react with resin components and degrade storage stability and adhesion at elevated temperatures.
An underfill material comprising epoxy resin, aromatic amine hardener, inorganic filler, and a compound with a triazine ring and an alkoxysilyl group, or a compound with a triazine ring and a primary amino group, is developed to enhance pot life and high-temperature adhesion to copper.
The proposed underfill material achieves excellent pot life and high-temperature adhesion to copper, ensuring reliable performance in semiconductor packages even at elevated temperatures.
Smart Images

Figure 0007673644000001 
Figure 0007673644000002 
Figure 0007673644000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an underfill material, a semiconductor package, and a method for manufacturing a semiconductor package. [Background technology]
[0002] In the field of encapsulation of various semiconductor elements used in semiconductor devices such as transistors and ICs (Integrated Circuits), encapsulation with resins has become mainstream in terms of productivity, manufacturing costs, etc. Epoxy resins are widely used as encapsulation resins because they have an excellent balance of properties such as workability, moldability, electrical properties, moisture resistance, heat resistance, mechanical properties, and adhesion to insert products.
[0003] In recent years, in the field of semiconductor devices, in order to accommodate the trend toward smaller and thinner packages, semiconductor devices that have bare chips mounted directly on wiring boards, so-called bare chip mounting, have become mainstream. Examples of bare chip mounting semiconductor devices include COB (Chip on Board), COG (Chip on Glass), and TCP (Tape Carrier Package).
[0004] In a flip-chip type semiconductor device in which a semiconductor element is bump-connected to a wiring board, a liquid resin composition is used as an underfill material to fill the gap between the bump-connected semiconductor element and the board. For example, Patent Document 1 describes an underfill material using a multifunctional epoxy resin and a curing agent containing a phenolic compound and an acid anhydride. The underfill material plays a role of protecting electronic components from temperature, humidity, and external mechanical forces.
[0005] In flip-chip type semiconductor devices, solder balls have traditionally been used primarily to connect semiconductor elements to substrates. However, as the number of terminals increases due to miniaturization and high integration of semiconductor devices, copper pillars with solder caps at the ends are increasingly being used instead of conventional solder balls. As a result, defects occur in which the underfill material peels off from the copper pillars during the process of connecting the semiconductor device to a motherboard or the like at high temperatures (e.g., 260°C) using a reflow furnace.
[0006] As a method for improving the adhesion of an epoxy resin composition to copper, for example, Patent Documents 2 to 6 describe epoxy resin compositions containing a compound that has excellent adhesion to copper. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-256646 A [Patent Document 2] JP 2007-2170 A [Patent Document 3] Patent Publication No. 2012-188629 [Patent Document 4] JP 2016-169300 A [Patent Document 5] JP 2016-34906 A [Patent Document 6] JP 2017-2289 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, when compounds that generally have excellent adhesion to copper are applied to underfill materials, they often react with resin components such as epoxy resins and hardeners, deteriorating the pot life, i.e., storage stability at room temperature. Furthermore, the adhesive strength of underfill materials to copper at high temperatures (e.g., 260°C) has not been verified until now.
[0009] In view of the above circumstances, an object of the present disclosure is to provide an underfill material that has an excellent pot life and, when cured, has excellent high-temperature adhesion to copper, as well as a semiconductor package including the cured underfill material and a method for manufacturing the same. [Means for solving the problem]
[0010] Means for solving the above problems include the following embodiments. <1> An underfill material comprising an epoxy resin, an aromatic amine curing agent, an inorganic filler, and a compound having a triazine ring and an alkoxysilyl group. <2> The compound having a triazine ring and an alkoxysilyl group has a melting point of 200° C. or lower. <1> The underfill material according to claim 1. <3> the compound having a triazine ring and an alkoxysilyl group further has a primary amino group; <1> or <2> The underfill material according to claim 1. <4> An underfill material comprising an epoxy resin, an aromatic amine curing agent, an inorganic filler, and a compound having a triazine ring and a primary amino group and a melting point of 200°C or lower. <5> A substrate, a semiconductor element disposed on the substrate, and a semiconductor element encapsulated therein. <1> ~ <4> and a cured product of the underfill material according to any one of claims 1 to 5. <6> A gap between a substrate and a semiconductor element disposed on the substrate is <1> ~ <5> 13. A method for manufacturing a semiconductor package, comprising: a step of filling with the underfill material described in any one of claims 1 to 12; and a step of curing the underfill material. Effect of the Invention
[0011] The present disclosure provides an underfill material that has an excellent pot life and, when cured, has excellent high-temperature adhesion to copper, as well as a semiconductor package including the cured underfill material and a method for manufacturing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present disclosure will be described in detail. However, the embodiments of the present disclosure are not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values and their ranges, and they do not limit the embodiments of the present disclosure.
[0013] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.
[0014] <Underfill material> The underfill material according to the first embodiment of the present disclosure contains an epoxy resin, an aromatic amine curing agent, an inorganic filler, and a compound having a triazine ring and an alkoxysilyl group (hereinafter also referred to as a "first triazine ring-containing compound"). An underfill material according to a second embodiment of the present disclosure contains an epoxy resin, an aromatic amine curing agent, an inorganic filler, and a compound having a triazine ring and a primary amino group and having a melting point of 200°C or less (hereinafter also referred to as a "second triazine ring-containing compound"). Hereinafter, the underfill material according to the first embodiment and the underfill material according to the second embodiment may be collectively referred to as the "underfill material of the present disclosure" or simply as the "underfill material."
[0015] The underfill material of the present disclosure has an excellent pot life and, when cured, has excellent high-temperature adhesion to copper. In this disclosure, high-temperature adhesion refers to adhesion at 260°C. The detailed reasons why the underfill material of the present disclosure has an excellent pot life and high-temperature adhesion to copper when cured are not necessarily clear, but are presumed to be as follows. The underfill material according to the first embodiment contains a compound having a triazine ring and an alkoxysilyl group (first triazine ring-containing compound). It is believed that the nitrogen atom in the triazine ring contributes to high-temperature adhesion to copper. In addition, due to the presence of the alkoxysilyl group, the first triazine ring-containing compound has excellent compatibility with epoxy resins and disperses well in the underfill material, so that it is believed that the high-temperature adhesion is good throughout the underfill material. Furthermore, when the first triazine ring-containing compound is used and an aromatic amine compound is used as a curing agent, the reactivity of the first triazine ring-containing compound and the aromatic amine compound with epoxy groups is not too high, so that the gelation proceeds relatively slowly and an excellent pot life is obtained. The underfill material according to the second embodiment contains a compound (second triazine ring-containing compound) having a triazine ring and a primary amino group and a melting point of 200°C or less. The nitrogen atom and the primary amino group in the triazine ring are considered to contribute to high-temperature adhesion to copper. In addition, since the compound has a melting point of 200°C or less, it is considered that the compound has excellent dispersibility in the epoxy resin during kneading (for example, about 25°C to 80°C), during filling in the gap between the element and the substrate (for example, about 100°C to 120°C), and during curing of the underfill material (for example, about 80°C to 200°C), and that the high-temperature adhesion is good throughout the underfill material. Furthermore, when the second triazine ring-containing compound is used and an aromatic amine compound is used as a curing agent, the reactivity of the second triazine ring-containing compound and the aromatic amine compound with the epoxy resin is not too high, so that the gelation proceeds relatively slowly and an excellent pot life is obtained.
[0016] The underfill material is preferably liquid at 25° C. In this disclosure, "liquid" refers to a substance that exhibits flowability and viscosity, and has a viscosity, which is a scale indicating viscosity, of 0.0001 Pa·s to 100 Pa·s. Additionally, "liquid state" refers to a state of liquid.
[0017] In this disclosure, the viscosity is the measured value when an EHD type rotational viscometer (for example, VISCONIC EHD type (product name) manufactured by Tokyo Keiki Co., Ltd.) is rotated at 10 revolutions per minute (10 rpm) for 1 minute at 25° C. The above measured value is obtained for a liquid kept at 25±1° C. using an EHD type rotational viscometer equipped with a cone rotor with a cone angle of 3° and a cone radius of 14 mm.
[0018] The viscosity of the underfill material is not particularly limited. In particular, from the viewpoint of high fluidity, the viscosity of the underfill material at 25°C is preferably 0.1 Pa·s to 100.0 Pa·s, more preferably 0.1 Pa·s to 50.0 Pa·s, and even more preferably 0.1 Pa·s to 30.0 Pa·s.
[0019] Furthermore, as an index of ease of filling narrow gaps of several tens to several hundreds of microns with the underfill material at around 100° C. to 120° C., the viscosity of the underfill material at 110° C. is preferably 0.20 Pa·s or less, and more preferably 0.15 Pa·s or less. The viscosity of the underfill material at 110° C. is measured using a rheometer (for example, AR2000 manufactured by TA Instruments, cone radius 20 mm, shear rate 32.5 / sec).
[0020] The pot life of the underfill material after being left at 25°C for 24 hours, as measured by the following method, is preferably 100% or less, more preferably 90% or less, even more preferably 80% or less, and particularly preferably 60% or less. There is no particular lower limit for the pot life, and the lower the value, the more preferable it is. The underfill material is left at 25°C for 24 hours, and then the viscosity at 25°C is measured using an E-type viscometer (for example, VISCONIC EHD model (product name) manufactured by Tokyo Keiki Co., Ltd.) (cone angle 3°, rotation speed 10 revolutions per minute (rpm)) (viscosity after leaving). However, for samples that cannot be measured at a rotation speed of 10 revolutions per minute (rpm) due to high viscosity, the measurement is made at 2.5 revolutions per minute (rpm). The pot life (%) is calculated as the rate of viscosity increase after leaving for 24 hours using the following formula. Pot life (%) = {(viscosity after standing - initial viscosity) / initial viscosity} x 100
[0021] The high temperature adhesive strength of the underfill material to copper (Cu), measured by the following method, is preferably 0.70 kgf or more, more preferably 0.80 kgf or more, and even more preferably 0.90 kgf or more. The higher the high temperature adhesive strength, the better.
[0022] The adhesive strength to copper can be measured, for example, as follows. A test piece is prepared by molding an underfill material to a diameter of 3 mm and a height of 3 mm on the surface of a copper plate, and a bond tester (e.g., DS100 model manufactured by DAGE) is used to apply a shear stress at a head speed of 50 μm / sec to measure the strength at which the molded product peels off from the copper plate. Specifically, the measurement can be performed by the method described in the Examples.
[0023] <Epoxy resin> The type of epoxy resin is not particularly limited, but the epoxy resin is preferably an epoxy resin having two or more epoxy groups in one molecule.
[0024] The epoxy resin may be solid or liquid at room temperature, and a solid epoxy resin and a liquid epoxy resin may be used in combination. From the viewpoint of reducing the viscosity of the underfill material, it is preferable to use an epoxy resin that is liquid at room temperature. From the viewpoint of fluidity during molding, it is preferable that the content of the solid epoxy resin is 20 mass% or less based on the total amount of the epoxy resin.
[0025] The type of epoxy resin is not particularly limited. Specific examples of the epoxy resin include novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; bisphenol type epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins; glycidylamine type epoxy resins such as N,N-diglycidylaniline, N,N-diglycidyltoluidine, diaminodiphenylmethane type glycidylamine, and aminophenol type glycidylamine; phenol aralkyl type epoxy resins having at least one selected from the group consisting of a phenylene skeleton and a biphenylene skeleton; aralkyl type epoxy resins such as naphthol aralkyl type epoxy resins having at least one selected from the group consisting of a phenylene skeleton and a biphenylene skeleton; haloaralkyl type epoxy resins having at least one selected from the group consisting of a naphthol aralkyl type epoxy resin; Hydroquinone type epoxy resins, biphenyl type epoxy resins, stilbene type epoxy resins, triphenolmethane type epoxy resins, triphenolpropane type epoxy resins, alkyl-modified triphenolmethane type epoxy resins, triazine nucleus-containing epoxy resins, dicyclopentadiene-modified phenol type epoxy resins, naphthol type epoxy resins, naphthalene type epoxy resins, alicyclic epoxy resins such as vinylcyclohexene dioxide, dicyclopentadiene oxide, and alicyclic diepoxy-adipate, and difunctional aliphatic epoxy compounds having two epoxy groups in the molecule such as alkylene glycol diglycidyl ether, poly(alkylene glycol) diglycidyl ether, and alkenylene glycol diglycidyl ether. The epoxy resins may be used alone or in combination of two or more.
[0026] When two or more kinds of epoxy resins are used, the two or more kinds of epoxy resins may be mixed in advance and then mixed with other components, or they may be mixed with other components without being mixed in advance.
[0027] The epoxy equivalent of the epoxy resin is not particularly limited. The epoxy equivalent of the epoxy resin may be 60 g / eq or more, 70 g / eq or more, or 90 g / eq or more. The epoxy equivalent of the epoxy resin may be 500 g / eq or less, 300 g / eq or less, or 200 g / eq or less. From the viewpoint of the balance of various properties such as moldability, reflow resistance, and electrical reliability, it is preferably 60 g / eq to 500 g / eq, more preferably 70 g / eq to 300 g / eq, and even more preferably 90 g / eq to 200 g / eq. The epoxy equivalent of the epoxy resin is a value measured by a method according to JIS K 7236:2009.
[0028] The content of the epoxy resin relative to the total mass of the underfill material is not particularly limited. The content of the epoxy resin relative to the total mass of the underfill material may be 0.5 mass% or more, or 2 mass% or more. The content of the epoxy resin relative to the total mass of the underfill material may be 50 mass% or less, 40 mass% or less, or 30 mass% or less. From the viewpoints of viscosity, glass transition temperature, heat resistance, etc., the content of the epoxy resin is preferably 0.5 mass% to 50 mass%, more preferably 2 mass% to 40 mass%, and even more preferably 5 mass% to 30 mass% relative to the total mass of the underfill material.
[0029] In one embodiment, from the viewpoint of injection property and reduction of thermal expansion coefficient when cured, the underfill material preferably contains at least one selected from the group consisting of bisphenol type epoxy resin, glycidylamine type epoxy resin, and naphthalene type epoxy resin.More preferably, the underfill material contains all of bisphenol type epoxy resin, glycidylamine type epoxy resin, and naphthalene type epoxy resin.
[0030] The type of bisphenol type epoxy resin is not particularly limited, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, etc. The bisphenol type epoxy resin may be used alone or in combination of two or more types. From the viewpoint of using the underfill material in a liquid state, it is preferable that the bisphenol type epoxy resin is liquid at room temperature (25°C). From the viewpoint of reducing the viscosity, it is preferable that the bisphenol type epoxy resin is a bisphenol F type epoxy resin.
[0031] When the underfill material contains a bisphenol type epoxy resin, the content of the bisphenol type epoxy resin is not particularly limited and can be selected according to the desired properties of the underfill material. For example, the content of the bisphenol F type epoxy resin may be 20 mass% or more, 30 mass% or more, or 40 mass% or more, based on the total mass of the epoxy resin. The content of the bisphenol F type epoxy resin may be less than 90 mass%, 80 mass% or less, or 70 mass% or less, based on the total mass of the epoxy resin. The content of the bisphenol F type epoxy resin may be 20 mass% or more and less than 90 mass%, 30 mass% to 80 mass%, or 40 mass% to 70 mass%, based on the total mass of the epoxy resin.
[0032] The type of glycidylamine type epoxy resin is not particularly limited. The glycidylamine type epoxy resin is preferably bifunctional or more, and from the viewpoint of improving heat resistance after curing, trifunctional or more (i.e., having three or more epoxy groups in one molecule) glycidylamine type epoxy resin is preferred. Examples of bifunctional glycidylamine type epoxy resins include N,N-diglycidylaniline and N,N-diglycidyl-o-toluidine. Examples of trifunctional or more glycidylamine type epoxy resins include triglycidyl-p-aminophenol and 4,4'-methylenebis[N,N-bis(oxiranylmethyl)aniline]. The glycidylamine type epoxy resin may be used alone or in combination of two or more. Among them, triglycidyl-p-aminophenol is preferred from the viewpoint of viscosity at room temperature (25°C).
[0033] From the viewpoint of reducing the viscosity of the underfill material, the molecular weight of the glycidylamine type epoxy resin is preferably 300 or less.
[0034] When the underfill material contains a glycidylamine type epoxy resin, the content of the glycidylamine type epoxy resin is not particularly limited. For example, the content of the glycidylamine type epoxy resin may be 10 mass% or more, 20 mass% or more, or 25 mass% or more, based on the total mass of the epoxy resin. The content of the glycidylamine type epoxy resin may be 60 mass% or less, 50 mass% or less, or 40 mass% or less, based on the total mass of the epoxy resin. The content of the glycidylamine type epoxy resin may be 10 mass% to 60 mass%, 20 mass% to 50 mass%, or 25 mass% to 40 mass%, based on the total mass of the epoxy resin.
[0035] The type of naphthalene type epoxy resin is not particularly limited, but from the viewpoint of reducing the thermal expansion coefficient, 1,6-bis(glycidyloxy)naphthalene is preferred.
[0036] When the underfill material contains a naphthalene type epoxy resin, the content of the naphthalene type epoxy resin is not particularly limited. For example, the content of the naphthalene type epoxy resin may be 10 mass% or more, or 15 mass% or more, based on the total mass of the epoxy resin. The content of the naphthalene type epoxy resin may be 30 mass% or less, or 25 mass% or less, based on the total mass of the epoxy resin. The content of the naphthalene type epoxy resin may be 10 mass% to 30 mass% or 15 mass% to 25 mass% based on the total mass of the epoxy resin.
[0037] <Aromatic amine curing agent> The type of aromatic amine curing agent is not particularly limited, and is preferably an aromatic amine compound having at least two or more of at least one selected from the group consisting of primary amino groups and secondary amino groups in one molecule, more preferably an aromatic amine compound having 2 to 4 of at least one selected from the group consisting of primary amino groups and secondary amino groups in one molecule, and even more preferably an aromatic amine compound having two of at least one selected from the group consisting of primary amino groups and secondary amino groups in one molecule. The aromatic amine curing agent is preferably liquid at 25°C.
[0038] Examples of aromatic amine curing agents include diethyltoluenediamines such as 3,5-diethyltoluene-2,4-diamine and 3,5-diethyltoluene-2,6-diamine, triethyldiaminobenzenes such as 1,3,5-triethyl-2,6-diaminobenzene, and diaminodiphenylmethanes such as 3,3'-diethyl-4,4'-diaminodiphenylmethane and 3,5,3',5'-tetramethyl-4,4'-diaminodiphenylmethane. The aromatic amine curing agents may be used alone or in combination of two or more.
[0039] Among these, from the viewpoint of storage stability, at least one selected from the group consisting of diaminodiphenylmethane and diethyltoluenediamine is preferred, and it is more preferred to use these in combination.
[0040] The active hydrogen equivalent of the aromatic amine curing agent is not particularly limited. The active hydrogen equivalent of the aromatic amine curing agent may be 20 g / eq or more, 30 g / eq or more, or 40 g / eq or more. The active hydrogen equivalent of the aromatic amine curing agent may be 200 g / eq or less, 100 g / eq or less, or 80 g / eq or less. From the viewpoint of achieving both reduced thermal stress and a high glass transition temperature (Tg) of the cured product, it is preferably 20 g / eq to 200 g / eq, more preferably 30 g / eq to 100 g / eq, and even more preferably 40 g / eq to 80 g / eq.
[0041] The underfill material may contain other curing agents in addition to the aromatic amine curing agent. Examples of the curing agent other than the aromatic amine curing agent include an aliphatic amine curing agent, a phenolic curing agent, an acid anhydride curing agent, an imidazole compound, an imidazoline compound, a polymercaptan curing agent, a polyaminoamide curing agent, an isocyanate curing agent, and a blocked isocyanate curing agent.
[0042] The content of the aromatic amine curing agent relative to the total mass of the curing agent is not particularly limited, and from the viewpoint of improving the pot life and high-temperature adhesion to copper when the cured product is formed, it is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. In particular, the total content of at least one selected from the group consisting of diaminodiphenylmethane and diethyltoluenediamine is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more relative to the total mass of the curing agent.
[0043] The equivalent ratio of the epoxy resin to the curing agent (including aromatic amine curing agent), that is, the ratio of the number of functional groups (active hydrogen in the case of an amine curing agent) in the curing agent to the number of epoxy groups in the epoxy resin (number of functional groups in the curing agent / number of epoxy groups in the epoxy resin) is not particularly limited. From the viewpoint of keeping the amount of unreacted components low, it is preferably set in the range of 0.5 to 2.0, and more preferably set in the range of 0.6 to 1.3. From the viewpoint of moldability and reflow resistance, it is more preferably set in the range of 0.8 to 1.2.
[0044] From the viewpoint of making the underfill material liquid at room temperature (25°C), it is preferable to select a curing agent such that the entire curing agent is liquid at room temperature. That is, when only one type of curing agent is used, it is preferable that the curing agent is liquid at room temperature. When a combination of two or more types of curing agents is used, the two or more types of curing agents may all be liquid at room temperature, or a combination of two or more types of curing agents, some of which are solid at room temperature, may be used such that the two or more types of curing agents become liquid at room temperature when mixed. When a curing agent that is solid at room temperature is used as the curing agent, the content of the curing agent is preferably 20 mass% or less with respect to the total mass of the curing agent from the viewpoint of fluidity.
[0045] <Inorganic filler> The type of inorganic filler is not particularly limited, and examples thereof include inorganic materials such as silica, glass, alumina, calcium carbonate, zirconium silicate, calcium silicate, silicon nitride, aluminum nitride, boron nitride, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, titania, talc, clay, and mica. Inorganic fillers having a flame retardant effect may be used. Examples of inorganic fillers having a flame retardant effect include aluminum hydroxide, magnesium hydroxide, composite metal hydroxides such as composite hydroxides of magnesium and zinc, and zinc borate. The inorganic fillers may be used alone or in combination of two or more. Among them, silica is preferred from the viewpoint of reducing the thermal expansion coefficient, and alumina is preferred from the viewpoint of improving thermal conductivity.
[0046] The content of the inorganic filler is not particularly limited. The content of the inorganic filler may be 30 mass% or more, 40 mass% or more, or 50 mass% or more, based on the total mass of the underfill material. The content of the inorganic filler may be 90 mass% or less, 80 mass% or less, or 75 mass% or less, based on the total mass of the underfill material. From the viewpoint of achieving both good fluidity and the desired effects of the inorganic filler, the content of the inorganic filler is preferably 30 mass% to 90 mass%, more preferably 40 mass% to 80 mass%, and even more preferably 50 mass% to 75 mass%, based on the total mass of the underfill material.
[0047] When the inorganic filler is particulate, its average particle diameter is not particularly limited. For example, the volume average particle diameter of the inorganic filler may be 0.2 μm or more, or 0.5 μm or more. The volume average particle diameter of the inorganic filler may be 20 μm or less, or 15 μm or less. The volume average particle diameter of the inorganic filler is preferably 0.2 μm to 20 μm, and more preferably 0.5 μm to 15 μm. When the volume average particle diameter is 0.2 μm or more, the increase in viscosity of the underfill material tends to be more suppressed. When the volume average particle diameter is 20 μm or less, the filling ability into narrow gaps tends to be more improved. The volume average particle diameter of the inorganic filler can be measured as the particle diameter (D50) when the cumulative volume from the small diameter side becomes 50% in the volume-based particle size distribution obtained by a laser scattering diffraction method particle size distribution measuring device.
[0048] <Triazine ring-containing compounds> -First triazine ring-containing compound- The first triazine ring-containing compound has a triazine ring and an alkoxysilyl group. The position of the nitrogen in the triazine ring is not particularly limited. That is, the triazine skeleton may be any of 1,2,3-triazine, 1,2,4-triazine, and 1,3,5-triazine.
[0049] The first triazine ring-containing compound is triazine (C3 H 3 N 3 ) has a structure in which at least one of the hydrogen atoms bonded to the three carbon atoms above is substituted with a monovalent group having an alkoxysilyl group. The substitution position of the monovalent group may be any of the three carbon atoms. The number of substitutions of the monovalent group may be any of 1 to 3, preferably 1 or 2, and more preferably 1.
[0050] When the number of substitutions of a monovalent group having an alkoxysilyl group in the first triazine ring-containing compound is 1 or 2, a substituent other than the monovalent group having an alkoxysilyl group may be bonded to a carbon atom on the triazine ring to which the monovalent group having an alkoxysilyl group is not bonded, or a substituent may not be bonded to the carbon atom.
[0051] The monovalent group having an alkoxysilyl group may be an alkoxysilyl group itself, or may be a monovalent group formed by bonding a linking group to the silicon atom of an alkoxysilyl group. When the monovalent group having an alkoxysilyl group is a monovalent group formed by bonding a linking group to the silicon atom of an alkoxysilyl group, the linking group may be, for example, a hydrocarbon group, or may be a hydrocarbon group having a heteroatom such as a nitrogen atom or an oxygen atom. The length of the linking group, that is, the number of atoms (not including hydrogen atoms, branched chains, or substituents) on the atomic chain present between the silicon atom of the alkoxysilyl group and the carbon atom on the triazine ring, may be, for example, 2 to 13, or may be 3 to 11.
[0052] The alkoxysilyl group is -Si(OR) 3 Here, R each independently represents a hydrogen atom or an alkyl group, and at least one of the three R is an alkyl group. Of the three R, it is preferable that two or more are alkyl groups, and it is more preferable that all three are alkyl groups. The alkyl groups represented by R are each independently preferably an alkyl group having 1 to 4 carbon atoms, more preferably an ethyl group or a methyl group, and further preferably an ethyl group.
[0053] The substituent other than the monovalent group having an alkoxysilyl group that may be bonded to the triazine ring is not particularly limited, and may include a halogen atom, an amino group, a hydroxy group, an arylamino group, an alkylamino group, etc. Among them, an amino group is preferred, a primary amino group or a secondary amino group is more preferred, and a primary amino group is even more preferred. The number of the substituent other than the monovalent group having an alkoxysilyl group is not particularly limited, and it is preferred that the number of the monovalent group having an alkoxysilyl group and the number of the substituent other than the monovalent group having an alkoxysilyl group are 3 in total.
[0054] A preferred example of the first triazine ring-containing compound is a compound represented by the following general formula (I).
[0055] [ka]
[0056] In formula (I), X represents a monovalent group having an alkoxysilyl group. Details of the monovalent group having an alkoxysilyl group in X are the same as those in the above-mentioned embodiment.
[0057] The molecular weight of the triazine ring-containing compound is not particularly limited, and may be, for example, 100-800, 200-700, or 300-600.
[0058] The melting point of the first triazine ring-containing compound is not particularly limited, and from the viewpoints of high-temperature adhesion and pot life, it is preferably 200° C. or less, more preferably 175° C. or less, and even more preferably 150° C. or less. From the viewpoints of handleability and dispersibility, the melting point of the first triazine ring-containing compound is preferably 0° C. or more, more preferably 10° C. or more, and even more preferably 25° C. or more. From the above viewpoints, the melting point of the first triazine ring-containing compound is preferably 0° C. to 200° C., more preferably 10° C. to 175° C., and even more preferably 25° C. to 150° C.
[0059] From the viewpoint of achieving both high-temperature adhesion to copper and an excellent pot life, the content of the first triazine ring-containing compound relative to the total mass of the underfill material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.20 mass% or more. Furthermore, from the viewpoint of suppressing an increase in the viscosity of the underfill material itself, the content of the first triazine ring-containing compound relative to the total mass of the underfill material is preferably 3.0 mass% or less, more preferably 2.0 mass% or less, and even more preferably 1.5 mass% or less. From the above viewpoints, the content of the first triazine ring-containing compound relative to the total mass of the underfill material is preferably 0.05 mass% to 3.0 mass%, more preferably 0.10 mass% to 2.0 mass%, and even more preferably 0.20 mass% to 1.5 mass%.
[0060] -Second triazine ring-containing compound- The second triazine ring-containing compound has a triazine ring and a primary amino group, and has a melting point of 200° C. or lower.
[0061] From the viewpoints of high-temperature adhesion and pot life, the melting point of the second triazine ring-containing compound is preferably 175° C. or lower, and more preferably 150° C. or lower. From the viewpoints of handleability and dispersibility, the melting point of the second triazine ring-containing compound is preferably 0° C. or higher, more preferably 10° C. or higher, and even more preferably 25° C. or higher. From the above viewpoints, the melting point of the second triazine ring-containing compound is preferably 0° C. to 200° C., more preferably 10° C. to 175° C., and even more preferably 25° C. to 150° C. The melting point of the triazine ring-containing compound can be measured using a melting point measuring device or the like.
[0062] The position of the nitrogen in the triazine ring is not particularly limited. That is, the triazine skeleton may be any of 1,2,3-triazine, 1,2,4-triazine, and 1,3,5-triazine.
[0063] The second triazine ring-containing compound is triazine (C 3 H 3 N 3 ) has a structure in which at least one of the hydrogen atoms bonded to the three carbon atoms above is substituted with a monovalent group having a primary amino group. The substitution position of the monovalent group may be any of the three carbon atoms. The number of substitutions of the monovalent group may be any of 1 to 3.
[0064] When the number of substitutions of the monovalent group having a primary amino group in the second triazine ring-containing compound is 1 or 2, a substituent other than the monovalent group having a primary amino group may be bonded to a carbon atom on the triazine ring to which the monovalent group having a primary amino group is not bonded, or a substituent may not be bonded to the carbon atom.
[0065] The monovalent group having a primary amino group may be a primary amino group itself, or may be a monovalent group formed by bonding a linking group to the nitrogen atom of a primary amino group. When the monovalent group having a primary amino group is a monovalent group formed by bonding a linking group to the nitrogen atom of a primary amino group, the linking group may be, for example, a hydrocarbon group, or may be a hydrocarbon group having a heteroatom such as a nitrogen atom or an oxygen atom. The length of the linking group, that is, the number of atoms (not including hydrogen atoms, branched chains, or substituents) on the atomic chain present between the nitrogen atom of the primary amino group and the carbon atom on the triazine ring, may be, for example, 1 to 10, or 1 to 5. It is preferable that the monovalent group having a primary amino group is a primary amino group itself.
[0066] The substituent other than the monovalent group having a primary amino group that may be bonded to the triazine ring is not particularly limited, and may include a halogen atom, an amino group, a hydroxy group, an arylamino group, an alkylamino group, and a monovalent group having an alkoxysilyl group, and from the viewpoint of pot life, a monovalent group having an alkoxysilyl group is preferred. The details of the monovalent group having an alkoxysilyl group are the same as the monovalent group having an alkoxysilyl group described in the first triazine ring-containing compound. The number of the substituent other than the monovalent group having a primary amino group is not particularly limited, and it is preferable that the number of the monovalent group having a primary amino group and the number of the substituent other than the monovalent group having a primary amino group are 3 in total.
[0067] A preferred example of the second triazine ring-containing compound is the compound represented by the above general formula (I).
[0068] From the viewpoint of achieving both high-temperature adhesion to copper and an excellent pot life, the content of the second triazine ring-containing compound relative to the total mass of the underfill material is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.20 mass% or more. Furthermore, from the viewpoint of suppressing an increase in the viscosity of the underfill material itself, the content of the second triazine ring-containing compound relative to the total mass of the underfill material is preferably 3.0 mass% or less, more preferably 2.0 mass% or less, and even more preferably 1.5 mass% or less. From the above viewpoints, the content of the second triazine ring-containing compound relative to the total mass of the underfill material is preferably 0.05 mass% to 3.0 mass%, more preferably 0.10 mass% to 2.0 mass%, and even more preferably 0.20 mass% to 1.5 mass%.
[0069] <Various additives> In addition to the above-mentioned components, the underfill material may contain various additives such as a curing accelerator, a stress relaxation agent, a coupling agent, an ion trapping agent, a bleed suppressant, a colorant, etc. In addition to the additives exemplified below, the underfill material may contain various additives known in the art as necessary.
[0070] (Cure accelerator) The underfill material may contain a curing accelerator. The type of the curing accelerator is not particularly limited and can be selected according to the types of epoxy resin and curing agent, the desired properties of the underfill material, etc. Specifically, cycloamidine compounds such as 1,8-diaza-bicyclo[5.4.0]undecene-7, 1,5-diaza-bicyclo[4.3.0]nonene, and 5,6-dibutylamino-1,8-diaza-bicyclo[5.4.0]undecene-7; cycloamidine compounds containing maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy- Compounds with intramolecular polarization formed by adding quinone compounds such as 1,4-benzoquinone, phenyl-1,4-benzoquinone, diazophenylmethane, phenolic resins, and other compounds with π bonds; tertiary amine compounds such as benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol; derivatives of tertiary amine compounds; 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole imidazole compounds such as 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole; derivatives of imidazole compounds; organic phosphine compounds such as tributylphosphine, methyldiphenylphosphine, triphenylphosphine, tris(4-methylphenyl)phosphine, diphenylphosphine, phenylphosphine; phosphorus compounds having intramolecular polarization obtained by adding a compound having a π bond such as maleic anhydride, the above-mentioned quinone compounds, diazophenylmethane, or a phenol resin to an organic phosphine compound; tetraphenylborate salts such as tetraphenylphosphonium tetraphenylborate, triphenylphosphonium tetraphenylborate, 2-ethyl-4-methylimidazolium tetraphenylborate, or N-methylmorpholinium tetraphenylborate; derivatives of tetraphenylborate salts; and tetraphenylborane complexes such as triphenylphosphine-triphenylborane complex and morpholine-triphenylborane complex.The curing accelerator may be used alone or in combination of two or more kinds.
[0071] When the underfill material contains a curing accelerator, the content of the curing accelerator is not particularly limited, but is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.8 to 5 parts by mass, per 100 parts by mass of the epoxy resin.
[0072] (Stress reliever) The underfill material may contain a stress relaxation agent. The type of stress relaxation agent is not particularly limited, and examples thereof include particles of thermoplastic elastomer, NR (natural rubber), NBR (acrylonitrile-butadiene rubber), acrylic rubber, urethane rubber, silicone rubber, etc. The stress relaxation agent may be used alone or in combination of two or more types.
[0073] When the underfill material contains a stress relaxation agent, the content of the stress relaxation agent is not particularly limited, but is preferably 0.1 to 30 parts by mass, and more preferably 1 to 15 parts by mass, per 100 parts by mass of the epoxy resin.
[0074] (Coupling Agent) The underfill material may contain a coupling agent. The type of coupling agent is not particularly limited, and examples thereof include silane compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, and vinylsilane; titanium compounds; aluminum chelate compounds; and aluminum / zirconium compounds. The coupling agents may be used alone or in combination of two or more.
[0075] When the underfill material contains a coupling agent, the content of the coupling agent is not particularly limited, but is preferably 0.01 to 5 parts by mass, and more preferably 0.02 to 2.5 parts by mass, per 100 parts by mass of the epoxy resin.
[0076] (Ion trapping agent) The underfill material may contain an ion trap agent. The type of the ion trap agent is not particularly limited, and examples thereof include compounds represented by the following general formula (VI-1) or the following general formula (VI-2).
[0077] Mg 1-a Al a (OH) 2 (CO 3 ) a / 2 ·uH 2 O (VI-1) (In the general formula (VI-1), a satisfies 0 < a ≤ 0.5, and u is a positive number.) BiO b (OH) c (NO 3 ) d (VI-2) (In the general formula (VI-2), b satisfies 0.9 ≤ b ≤ 1.1, c satisfies 0.6 ≤ c ≤ 0.8, and d satisfies 0.2 ≤ d ≤ 0.4.)
[0078] The ion trap agent is commercially available. As the compound represented by the general formula (VI-1), for example, "DHT-4A" (trade name, manufactured by Kyowa Chemical Industry Co., Ltd.) is commercially available. Further, as the compound represented by the general formula (VI-2), for example, "IXE500" (trade name, manufactured by Toagosei Co., Ltd.) is commercially available.
[0079] In addition, as ion trap agents other than the above, hydrous oxides of elements selected from magnesium, aluminum, titanium, zirconium, antimony, etc. can be mentioned. The ion trap agent may be used alone or in combination of two or more.
[0080] When the underfill material contains an ion trapping agent, the content of the ion trapping agent is not particularly limited, and from the viewpoint of realizing sufficient moisture resistance reliability, it is preferably 1 part by mass or more, and more preferably 2 parts by mass or more, relative to 100 parts by mass of epoxy resin. From the viewpoint of fully exerting the effects of other components, the content of the ion trapping agent is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of epoxy resin. From the above viewpoints, the content of the ion trapping agent is preferably 1 part by mass to 15 parts by mass, more preferably 1 part by mass to 10 parts by mass, and even more preferably 2 parts by mass to 5 parts by mass, relative to 100 parts by mass of epoxy resin.
[0081] The average particle size of the ion trapping agent is preferably 0.1 μm to 3.0 μm, and the maximum particle size is preferably 10 μm or less. The average particle size of the ion trapping agent can be measured in the same manner as in the case of the inorganic filler.
[0082] (bleed inhibitor) The underfill material may contain a bleed inhibitor. The type of bleed inhibitor is not particularly limited, and examples thereof include nonionic surfactants and silicone-modified epoxy resins. The bleed inhibitor may be used alone or in combination of two or more.
[0083] The content of the bleed inhibitor is not particularly limited, and is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 2 parts by mass, and even more preferably 0.3 to 1 part by mass, relative to 100 parts by mass of the epoxy resin.
[0084] (Coloring agent) The underfill material may contain a colorant. The type of colorant is not particularly limited, and examples include carbon black, organic dyes, organic pigments, titanium oxide, red lead, red iron oxide, etc. The colorants may be used alone or in combination of two or more.
[0085] When the underfill material contains a colorant, the content of the colorant is not particularly limited, but is preferably 0.001 to 1 part by mass, and more preferably 0.02 to 0.5 parts by mass, based on the total amount of the underfill material.
[0086] [Method of preparing underfill material] The underfill material can be obtained, for example, by stirring, melting, mixing, dispersing, etc., each component, either collectively or separately, while optionally applying a heat treatment. The device for mixing, stirring, dispersing, etc., these components is not particularly limited, and examples thereof include a crusher equipped with a stirrer, a heater, etc., a three-roll mill, a ball mill, a planetary mixer, a bead mill, etc. The underfill material can be obtained by mixing and kneading each component using such a device, and degassing as necessary.
[0087] [Applications of underfill materials] The underfill material can be used in various mounting techniques. In particular, the underfill material of the present disclosure can be suitably used as an underfill material for use in flip-chip mounting techniques, i.e., for filling gaps between a semiconductor element and a substrate that are joined by bumps or the like. The underfill material of the present disclosure can also be suitably used as an underfill material for use in flip-chip mounting techniques that use copper pillars.
[0088] The types of the semiconductor element and the substrate are not particularly limited and may be appropriately selected from those commonly used in the field of semiconductor packages. The method of filling the gap between the semiconductor element and the substrate with the underfill material is not particularly limited.
[0089] <Semiconductor Package> The semiconductor package of the present disclosure includes a substrate, a semiconductor element disposed on the substrate, and a cured product of the underfill material of the present disclosure that encapsulates the semiconductor element.
[0090] In the semiconductor package, the types of the semiconductor element and the substrate are not particularly limited and can be appropriately selected from those generally used in the field of semiconductor packages. From the viewpoint that the underfill material of the present disclosure is particularly useful, the semiconductor package is preferably a flip-chip mounting type semiconductor package, and more preferably a flip-chip mounting type semiconductor package using copper pillars as bumps for connecting the semiconductor element and the substrate.
[0091] <Semiconductor package manufacturing method> The method for manufacturing a semiconductor package of the present disclosure includes a step of filling a gap between a substrate and a semiconductor element disposed on the substrate with the underfill material of the present disclosure, and a step of curing the underfill material.
[0092] The details of the semiconductor package are as described above. There are no particular limitations on the method of filling the gap between the semiconductor element and the substrate with the underfill material and the method of curing the underfill material after filling. For example, there is a post-insertion method in which, after connecting the semiconductor element and the substrate, the underfill material is applied to the gap between the semiconductor element and the substrate by utilizing the capillary phenomenon, and then the curing reaction of the underfill material is carried out, and a pre-application method in which the underfill material is applied to at least one surface of the semiconductor element and the substrate first, and when the semiconductor element is connected to the substrate by thermocompression bonding, the connection of the semiconductor element and the substrate and the curing reaction of the underfill material are carried out all at once. Examples of the method of applying the underfill material include a casting method, a dispensing method, and a printing method.
[0093] The curing conditions for the underfill material are not particularly limited, and it is preferable to heat the material at 80° C. to 200° C. for 1 minute to 150 minutes, for example. EXAMPLES
[0094] The above-mentioned embodiment will be specifically described below using examples, but the scope of the embodiment of the present disclosure is not limited to these examples.
[0095] [Preparation of Underfill Material] The components shown in Tables 1 and 2 were mixed in the amounts shown in the tables to prepare underfill materials. Details of each component are as follows. In Tables 1 and 2, blank spaces indicate that the component was not mixed.
[0096] Epoxy resin 1: Liquid bisphenol F type epoxy resin, epoxy equivalent: 160g / eq, product name "Epotohto YDF-8170C", Nippon Steel Chemical & Material Co., Ltd. Epoxy resin 2: Triglycidyl-p-aminophenol, epoxy equivalent: 95g / eq, product name "jER 630", Mitsubishi Chemical Corporation Epoxy resin 3...1,6-bis(glycidyloxy)naphthalene, epoxy equivalent: 143g / eq, product name "Epiclon HP-4023D", DIC Corporation
[0097] Hardener 1…Diethyltoluenediamine, product name “jER Cure W”, active hydrogen equivalent: 45g / eq, Mitsubishi Chemical Corporation Hardener 2: 3,3'-diethyl-4,4'-diaminodiphenylmethane, product name "KAYAHARD AA", active hydrogen equivalent: 63g / eq, Nippon Kayaku Co., Ltd. Hardener 3: 3,4-dimethyl-6-(2-methyl-1-propenyl)-4-cyclohexene-1,2-dicarboxylic anhydride, product name "YH-306", anhydride equivalent: 234g / eq, Mitsubishi Chemical Corporation Hardener 4: 2-allylphenol-formaldehyde polycondensate, product name "MEH-8000H", active hydrogen equivalent: 140g / eq, Meiwa Kasei Co., Ltd.
[0098] Curing accelerator 1...Triphenylphosphine Curing accelerator 2...2-phenyl-4-methyl-5-hydroxymethylimidazole Ion trapping agent: Compound represented by general formula (VI-2), product name: "IXE500", Toagosei Co., Ltd. Colorant: Carbon black, product name "MA-100", Mitsubishi Chemical Corporation Inorganic filler: Spherical silica with the surface treated with an epoxy silane coupling agent, product name "SE2200-SEJ", volume average particle size 0.6 μm, Admatechs Co., Ltd.
[0099] The following commercially available compounds were used as test compounds.
[0100] Compound 1...Triazine derivative (product name: VD-5, Shikoku Chemical Industry Co., Ltd., compound shown below, R is a divalent linking group)
[0101] [ka]
[0102] Compound 2: Melamine (compound below)
[0103] [ka]
[0104] Compound 3...6-phenyl-1,3,5-triazine-2,4-diamine (compound below)
[0105] [ka]
[0106] Compound 4...3-amino-1,2,4-triazole (compound below)
[0107] [ka]
[0108] Compound 5...5-amino-1H-tetrazole (compound shown below)
[0109] [ka]
[0110] Compound 6...1,2,3-benzotriazole (product name: BT-120, Johoku Chemical Industry Co., Ltd., compound shown below)
[0111] [ka]
[0112] Compound 7...1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole (product name: BT-LX, Johoku Chemical Industry Co., Ltd., compound shown below)
[0113] [ka]
[0114] [Table 1]
[0115] [Table 2]
[0116] In Tables 1 and 2, the amount of curing agent is shown as a mass ratio when the total mass of the curing agent is taken as 100. The amounts of colorant, inorganic filler, and test compound are shown as the content (mass%) relative to the total mass of the underfill material. The amounts of curing accelerator and ion trapping agent are shown in parts by mass of each component relative to a total of 100 parts by mass of epoxy resin. In the above underfill material, the ratio of the number of active hydrogens in the curing agent to the number of epoxy groups in the epoxy resin (number of active hydrogens in the curing agent / number of epoxy groups in the epoxy resin) is 1.0.
[0117] [Evaluation of Viscosity] The viscosity (Pa·s) of the underfill material at 25°C was measured using an E-type viscometer (Tokyo Keiki Co., Ltd., VISCONIC EHD model (product name)) (cone angle 3°, rotation speed: 10 revolutions / min) per minute (rpm).
[0118] [Pot life evaluation] The underfill material was left to stand at 25°C for 24 hours, and then the viscosity at 25°C was measured using an E-type viscometer (Tokyo Keiki Co., Ltd., VISCONIC EHD model (product name)) (cone angle 3°, rotation speed 10 revolutions per minute (rpm)) (viscosity after standing). However, for samples with high viscosity that could not be measured at a rotation speed of 10 revolutions per minute (rpm), the measurement was made at 2.5 revolutions per minute (rpm). The pot life (%) was calculated as the viscosity increase rate after being left to stand for 24 hours using the following formula. Pot life (%) = {(viscosity after standing - initial viscosity) / initial viscosity} x 100
[0119] [Evaluation of adhesive strength at 25°C or 260°C] Adhesion to copper (Cu) Test pieces were prepared by molding the underfill material onto the surface of a copper plate to a diameter of 3 mm and a height of 3 mm. Using a bond tester DS100 (manufactured by DAGE), shear stress was applied at a head speed of 50 μm / sec at 25°C or 260°C to measure the strength at which the molded piece peeled off from the copper plate.
[0120] The evaluation results are shown in Tables 3 and 4. In Tables 3 and 4, "-" indicates not applicable. "Not measurable" in the pot life evaluation indicates that the viscosity increased significantly and measurement was not possible.
[0121] [Table 3]
[0122] [Table 4]
[0123] As shown in Tables 3 and 4, the underfill materials of Examples 1 to 6 containing Test Compound 1 were excellent in pot life and adhesion to copper at 260°C. On the other hand, the underfill material of Comparative Example 1, which did not contain test compound 1, had slightly high adhesion to copper at 25° C., but poor adhesion to copper at 260° C. The underfill materials of Comparative Examples 2 to 7, which contained various test compounds, had significantly poor pot lives and poor adhesion to copper at 260° C. The underfill materials of Comparative Examples 8 and 9, which contained test compound 1 but replaced the curing agent with curing agent 3 or 4, also had poor pot lives and poor adhesion to copper at 260° C.
[0124] The disclosure of Japanese Patent Application No. 2020-009238 is incorporated herein by reference in its entirety. All publications, patent applications, and standards mentioned in this specification are incorporated by reference into this specification to the same extent as if each individual publication, patent application, and standard was specifically and individually indicated to be incorporated by reference.
Claims
1. Epoxy resin, a curing agent comprising an aromatic amine curing agent; An inorganic filler; a compound having a triazine ring and an alkoxysilyl group; Contains The underfill material, wherein the aromatic amine curing agent comprises at least one selected from the group consisting of substituted or unsubstituted diaminodiphenylmethane and diethyltoluenediamine.
2. 2. The underfill material according to claim 1, wherein the compound having a triazine ring and an alkoxysilyl group has a melting point of 200[deg.] C. or lower.
3. 3. The underfill material according to claim 1, wherein the compound having a triazine ring and an alkoxysilyl group further has a primary amino group.
4. An underfill material described in any one of claims 1 to 3, wherein the content of the compound having a triazine ring and an alkoxysilyl group is 0.05 mass% to 1.5 mass% relative to the total mass of the underfill material.
5. An underfill material described in any one of claims 1 to 4, wherein the ratio of the number of functional groups in the curing agent to the number of epoxy groups in the epoxy resin (number of functional groups in the curing agent / number of epoxy groups in the epoxy resin) is 0.5 to 2.
0.
6. An underfill material described in any one of claims 1 to 5, further containing an inorganic filler in an amount of 30 mass% or more relative to the total mass of the underfill material.
7. Epoxy resin, a curing agent comprising an aromatic amine curing agent; An inorganic filler; a compound having a triazine ring and a primary amino group and having a melting point of 200° C. or lower; Contains The underfill material, wherein the aromatic amine curing agent comprises at least one selected from the group consisting of substituted or unsubstituted diaminodiphenylmethane and diethyltoluenediamine.
8. An underfill material as described in claim 7, wherein the content of the compound having a triazine ring and a primary amino group and having a melting point of 200°C or less is 0.05 mass% to 1.5 mass% relative to the total mass of the underfill material.
9. An underfill material described in claim 7 or claim 8, wherein the ratio of the number of functional groups in the curing agent to the number of epoxy groups in the epoxy resin (number of functional groups in the curing agent / number of epoxy groups in the epoxy resin) is 0.5 to 2.
0.
10. An underfill material described in any one of claims 7 to 9, further containing an inorganic filler in an amount of 30 mass% or more relative to the total mass of the underfill material.
11. A semiconductor package comprising: a substrate; a semiconductor element disposed on the substrate; and a cured product of the underfill material according to any one of claims 1 to 10, which seals the semiconductor element.
12. A method for manufacturing a semiconductor package, comprising: a step of filling a gap between a substrate and a semiconductor element disposed on the substrate with the underfill material according to any one of claims 1 to 10; and a step of hardening the underfill material.
Citation Information
Patent Citations
Liquid epoxy resin composition and electronic component device
JP2004210901A
Resin composition for underfilling, and semiconductor device
JP2004256646A
Epoxy resin composition, copper clad laminate board, adhesive film, cover lay, and printed wiring board
JP2007002170A
Silicone underfill material for flip chip type semiconductor device and flip chip type semiconductor device using the same
JP2011001412A
Curable resin composition and semiconductor device using the same
JP2012188629A